Adjuvant therapies for HIV‐associated neurocognitive disorders. (23rd October 2014) - McGuire, Jennifer L.; Barrett, Jeffrey S.; Vezina, Heather E.; Spitsin, Sergei; Douglas, Steven D.
Abstract Objective HIV‐associated neurocognitive disorder (HAND) is a frequent and heterogeneous complication of HIV, affecting nearly 50% of infected individuals in the combined antiretroviral therapy (cART) era. This is a particularly devastating statistic because the diagnosis of HAND confers an increased risk of HIV‐associated morbidity and mortality in affected patients. While cART is helpful in the treatment of the more severe forms of HAND, there is a therapeutic gap in the milder forms of HAND, where cART is less effective. Multiple adjuvant therapies with various mechanisms of action have been studied (N‐methyl D‐aspartate [NMDA]‐receptor antagonists, MAO‐B inhibitors, tetracycline‐class antibiotics, and others), but none have shown a clear positive effect in HAND. While this lack of efficacy may be because the appropriate therapeutic targets have not yet been determined, we aimed to discuss that study results may also influenced by clinical trial design. Methods This report is a systematic review of clinical trials of adjuvant therapies for HAND performed from January 1996 through June 2014. Results Possible drawbacks in study design, including lack of standardized case definitions, poorly defined target populations, inappropriate dose selection and measurable outcomes, and brief study durations may have masked true underlying mechanistic effects of previously investigated adjuvant therapies for HAND in specific patient populations. Conclusions A proposal for streamlining and maximizing the likelihood of success in future clinical studies using a 'learning and confirming' investigational paradigm, incorporating stronger adaptive Phase I/II study designs, computerized modeling, and population/goal of treatment‐specific Phase III clinical trials is presented.